Aging motor performance in a dual task control - Gehring, Paula Regina; Bertolassi, Marco Antonio; Nunes, Marcelo Eduardo Souza; Basso, Luciano; Meira Júnior, Cássio de Miranda; Santos, Suely dos (Brazilian journal of physical education and sport, 2009)
Motor behavior literature about aging process has systematically shown differences in performance between young and old populations. Experimental designs involve groups of old, ranging from 60 to even over 90 years old, while groups of young people are usually represented by participants in their early 20's. Such procedure could hide developmental changes with the advance of age and, consequently, could lead to results misinterpretation. Therefore the main purpose of this study was to verify whether there is an age effect on the performance in a motor task. It was used an apparatus enabling a linear positioning combined with a manual force control task. Participants performed the motor task receiving verbal knowledge of result in ten trials about the immediately finished trial that provided information about accomplishing the goal of 20% of the maximum force and 35cm of displacement. Performance was measured by absolute errors. The sample comprised 150 participants raging from 60 to 86 years old, which performed the task blinded folded and with non-dominant hand. Participants were divided in three age groups (60, 70, 80 years), and performance was also compared with a young group (21 to 30 years old). Correlation analyses show a significant but low age effect in distance control, and there was no difference in performance among older groups (except G20 and G80). Despite instructor's empirical observation about differences in motor performance with aging, apart from fitness, surprisingly, the present study did not show such age effect on the performance of this particular motor task. Perhaps, considering that these participants were physically active, possible differences in motor performance due to development were overcome by their lifestyle.